Building coherent monitoring and evaluation plans with the Evaluation Planning Tool for global health. (30th June 2022) - Roberton, Timothy; Sawadogo-Lewis, Talata
ABSTRACT: Practitioners in global health are called to monitor and evaluate their projects. This keeps projects on track, it meets donor and public demand, and it is a key mechanism by which global health organizations hold themselves accountable and improve their community of practice. However, monitoring and evaluation (M&E) is time- and resource-consuming, bringing into question whether the effort expended on M&E is worth it. While there has been a shift towards emphasizing the learning aspect of M&E, non-governmental organizations (NGOs) and other actors still struggle to get value from their efforts. One reason for this is that M&E plans are often not coherent or employed to their full potential. Theories of change, indicator lists, and data collection become a series of disjointed efforts that do not tie together. They become tick-the-box exercises to satisfy donors rather than a logical approach to draw meaningful findings for stakeholders, governments, and local communities. In this paper, we propose a step-by-step approach to utilizing M&E tools to their fullest potential, including: (1) a clearly defined theory of change that captures all program pathways and shows all intermediate objectives needed to achieve impact, (2) indicators which directly reflect the intermediate and ultimate objectives in the theory of change, and (3) a data collection plan which includes appropriate methods to measure indicators and address the questions stakeholders want answered. We make the case for a simpler, more coherent approach to M&E and propose a new tool to help practitioners more easily develop evaluation plans that are rigorous, practical, and worth the effort.